Facial Porokeratosis – An Uncommon Presentation of an Uncommon Disease - Siddiqui, Moin Ahmad (Nepal Journal of Dermatology, Venereology & Leprology, 2025)
Porokeratosis is an uncommon keratinization disorder characterized by keratotic papules or annular plaques with elevated borders. It has distinctive histological findings. Porokeratosis with exclusive facial lesions is seldom reported. A 25-year-old unmarried female presented with multiple, asymptomatic, brownish plaques ranging in size from 3-6 mm over the face involving both cheeks, the dorsum of the nose, and the forehead. Examination of hair, mucosae, and nails was normal. Systemic examination was unremarkable. Histopathology revealed the presence of coronoid lamella atop a disrupted stratum granulosum and dyskeratotic keratinocytes. These features confirmed the diagnosis of porokeratosis. She was prescribed topical tazarotene gel for application at night for 6 weeks. The patient returned after 1 month with some improvement, and after that lost to follow-up.